Beyond Social Norms - Santos, Marta Almeida dos (2025)
Santos, M. A. D., Naranjo-Zolotov, M., Long, L. A. N., Acedo, A., Ashofteh, A., & Aparicio, M. (2025). Beyond Social Norms: Exploring The Drivers of Youth's Political Participation Via Social Media. Emerging Science Journal, 9(2), 588-602. https://doi.org/10.28991/ESJ-2025-09-02-05 --- This work was supported by national funds through FCT (Fundação para a Ciência e Tecnologia), under the project UIDB/04152/2020 (https://doi.org/10.54499/UIDB/04152/2020) -Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.